Long-term perimetric fluctuation in patients with different stages of glaucoma. Issue 2 (31st July 2010) - Fogagnolo, Paolo; Sangermani, Chiara; Oddone, Francesco; Frezzotti, Paolo; Iester, Michele; Figus, Michele; Ferreras, Antonio; Romano, Simona; Gandolfi, Stefano; Centofanti, Marco; Rossetti, Luca; Orzalesi, Nicola
Abstract : Aim: To evaluate the long-term perimetric fluctuation (LF) in patients with different stages of glaucoma according to the Glaucoma Staging System 2 (GSS2). Methods: This multicentre retrospective study included 161 eyes of 161 stable glaucoma patients undergoing four visual-field tests (Humphrey SITA-Standard program over the central 24° or 30°) over a 2-year period. For each patient, the stage of the disease was classified according to GSS2. LF was then calculated as the mean of the standard deviations of point-to-point threshold sensitivities in the four repetitions. LF in GSS2 stages was compared using the t test. Results: LF progressively increased from stage 0 to stage 4, and then decreased at stage 5. Stage 4 had a peak of 3.19±0.94 dB, with statistically significant differences compared with all the other stages. The lowest LF (1.65±0.60 dB) was found for normal subjects, whereas similar data were found for borderline patients and those at stages 1 and 5 (2.09±0.58, 2.13±0.57 and 2.22±0.89 dB, respectively; p>0.13). Visual fields with generalised defects had a lower LF (1.90±0.81) than those with mixed (2.84±0.87, p=0.0003) and localised (2.63±0.72, p=0.004) defects. Conclusions: In this study, the authors showed that the lower the visual-field defect, the lower was LF, except at stage 5 of GSS2. As test–retest changes exceeding LF could represent a sign of progression, the authors suggest that clinicians using this classification system calculate LF, in order to better differentiate true progression from variability.